Case Report to Analysethe Efficacy of Jalaukavcharana (Leech Therapy) in Management of Madhumehaj Vrana (Diabetic Foot Ulcer) - Balyogeshwar Sharma; Khyati (Research Highlights in Disease and Health Research Vol. 9, 2023)
The present case study highlights the effect of Jalokavcharana in Diabetic Foot Ulcer (Madhumehaj Vrana). Diabetic Foot Ulcer is the major complication of Diabetes Mellitus. It is a syndrome involving Neuropathy, Ischemia, infection, poor wound healing due to increased Blood Sugar Level, minor trauma, cutaneous ulceration, gangrene. 85% of diabetic foot ulcer leads to Amputation, resulting in disability. There is a need of accessible affordable and fast technique for management of Madhumehaj Vrana. Raktamokshana throug Chronic Madhumehaj Vrana h Jalauka is such a powerful Para surgical Procedure which can be the boon to society. Acharya Sushruta made it very clear that anyone who is Parama Sukumara can perform Jalaukavcharana with ease. This procedure removes deeply ingrained vitiated doshas and enhances blood circulation, which speeds up the healing of ulcers. Jalauka showed its Vrana Shodhana and Ropana effects by removing the vitiated doshas from the affected region and increased healing by improving the blood circulation and decreasing inflammation of the planter region of the foot.